Oleanolic acid and its synthetic derivatives for the prevention and therapy of cancer: Preclinical and clinical evidence - Shanmugam, M.; Dai, X.; Kumar, Alan Prem; Tan, B.; Sethi, G.; Bishayee, A. (Elsevier, 2014)
Oleanolic acid (OA, 3ß-hydroxyolean-12-en-28-oic acid) is a ubiquitous pentacyclic multifunctional triterpenoid, widely found in several dietary and medicinal plants. Natural and synthetic OA derivatives can modulate multiple signaling pathways including nuclear factor-?B, AKT, signal transducer and activator of transcription 3, mammalian target of rapamycin, caspases, intercellular adhesion molecule 1, vascular endothelial growth factor, and poly (ADP-ribose) polymerase in a variety of tumor cells. Importantly, synthetic derivative of OA, 2-cyano-3,12-dioxoolean-1,9-dien-28-oic acid (CDDO), and its C-28 methyl ester (CDDO-Me) and C28 imidazole (CDDO-Im) have demonstrated potent antiangiogenic and antitumor activities in rodent cancer models. These agents are presently under evaluation in phase I studies in cancer patients. This review summarizes the diverse molecular targets of OA and its derivatives and also provides clear evidence on their promising potential in preclinical and clinical situations.